Exploring Students’ Ability in Using Preposition “By” and “With” - priyanti, wiwik (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2019)
In this study, the writer wants to know how well the students’ ability of second grade at SMP Muhammadiyah Aimas in understanding preposition “by” and “with”. Why the writer took this problem because the prepositions are important classes of function word in English. The population of this study are the second grade (A are 24 students and B are 25 students) of SMP Muhammadiyah Aimas. The total number of the students are 49 students. the writer chose probability sampling to get samples. Because, SMP Muhammadiyah only has two class of second grade (2A and 2B). Based on information from the English teacher there, the class both have same ability in learning English.The writer gives tests to the students without a treatment. Because, the writer want to know the real students’ ability in understanding its.The writer gave fifty (50) items for the test. The kind of instrument is fill the blanks. And the writer used percentage form x 100% to analysed the data. From twenty-four (24) students the writer got result of students’ ability in using preposition “by” = 16.2%, students’ ability in using preposition “with” = 11.6%, and calculated in overall their ability was 56% on preposition “by” and “with” included in bad category.